Development of Android-Based Learning Media for Islamic Cultural History to Improve Students’ Learning Outcomes - Ramadhana Agung Pratama; Adi Fadli; Ismail Ismail; Wildan Wildan (LP. Ma'arif Janggan Magetan, 2026)
The integration of digital technology in history education is still limited in many Islamic secondary schools, where learning is often dominated by text-based instruction that reduces student engagement and learning outcomes. This study aims to develop and evaluate Android-based learning media for Islamic Cultural History to improve student learning outcomes at Madrasah Aliyah Qamarul Huda Bagu. This research method uses a research and development (R&D) approach with the ADDIE model, followed by a quasi-experimental pre-test and post-test design to test the effectiveness of the learning. Data were collected through expert validation instruments, student response questionnaires, and achievement tests, and analyzed using descriptive statistics, normalized gain (N-gain), and comparative analysis of pre-test and post-test scores. The results indicate that the developed Android-based learning media is valid and practical, as confirmed by expert assessments and positive student responses. Furthermore, statistical analysis shows a significant increase in student learning outcomes after the media implementation, with the improvement in learning outcomes being in the moderate to high effectiveness category. These findings suggest that Android-based learning media can serve as an effective teaching tool that enhances conceptual understanding and active engagement in learning Islamic Cultural History.